2000
DOI: 10.1055/s-2000-6667
|View full text |Cite
|
Sign up to set email alerts
|

An Enantiospecific Pauson-Khand Reaction

Abstract: The use of optically pure heterobimetallic alkyne complexes for the synthesis of enantiopure cyclopentenones is described. The inherent chirality of the complexes has been used to effect high levels of stereocontrol in transformations giving optically enriched organic end products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…After chromatographic purification, orange-colored complexes 1 − 6 were isolated in yields comparable to those reported in the literature for other alkynes. 4a, For N -(phenylpropionyl)-4-benzyloxazolidinone (second entry of Table ) only, the formation of the heterobimetallic complex could not be observed, probably because of the increased steric hindrance of the substrate . The diastereoselectivities of the complexation reactions of the two chiral oxazolidinone derivatives (first and third entries of Table ) were very similar, and the diastereomeric complexes ( 1a / 1b and 2a / 2b , respectively) were easily separated by column chromatography in both cases.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…After chromatographic purification, orange-colored complexes 1 − 6 were isolated in yields comparable to those reported in the literature for other alkynes. 4a, For N -(phenylpropionyl)-4-benzyloxazolidinone (second entry of Table ) only, the formation of the heterobimetallic complex could not be observed, probably because of the increased steric hindrance of the substrate . The diastereoselectivities of the complexation reactions of the two chiral oxazolidinone derivatives (first and third entries of Table ) were very similar, and the diastereomeric complexes ( 1a / 1b and 2a / 2b , respectively) were easily separated by column chromatography in both cases.…”
supporting
confidence: 58%
“…Recently, Christie et al have reported that, upon replacing one of the Co(CO) 3 groups of an alkyne−dicobalt(hexacarbonyl) complex by an isoelectronic MoCp(CO) 2 moiety, the resulting heterobimetallic complexes still are active partners in intermolecular Pauson−Khand cycloadditions with norbornadiene, giving rise to the expected exo -fused adducts. Moreover, the chirality of the metal−alkyne tetrahedral core introduced by this substitution can be used to induce high levels of stereocontrol in the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation